PROCESS APPROACH TO MANAGEMENT IN THE ORGANIZATIONS OF HOUSING AND UTILITY INFRASTRUSTURE SPHERE - Nikolay K. Kemaykin; Mikhail N. Pavlenkov (Статистика и экономика, 2016)
The application of process approach to management of an enterprise in the sphere ofhousing and utility infrastructure is examined inthe article. The prevalence of process approachapplication in housing and utility is describedthere. The authors estimated the inﬂ uence of transition to process approach on the qualityof provided services by the example of one ofthe management companies. The authors offered the methodology on the basis of moneyﬂows compounding procedure, which is usedfor the estimation of economic effect from the inculcation of business processes in management companies.